PEMBELAJARAN MEDIA VISUAL BAHASA INGGRIS UNTUK ANAK-ANAK PAUD/TK DI SURAKARTA - Prasetyo, Johnny (Institut Seni Indoensia Surakarta, 2015)
The swift technological advances can make a great contribution in the field of education. Because of this, the experts in education have a wish to improve the system of learning models. One of the learning models developed recently is the learning model made use of visual media. Due to that, the learning model in PAUD/TK is beginning to be developed into visual media. The visual media developed is in English to make the teacher easier in mastering the subject matter of the language. The subject matter of the lesson could be in the form of pictures, video, film and so on. The research entitled The Innovative Technique of Visual Media in Learning English for PAUD/TK in Surakarta is qualitativedescriptive in nature. The goal of this research is to describe the facts, natures and relations of the phenomena systematically, factually, and accurately. The results of the research are a visual media learning model for English for PAUD/TK students and the usage of the visual mediaKeywords: visual media, English, PAUD (play group), TK (elementary school), model.